2013
DOI: 10.11112/jksmi.2013.17.3.001
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Evaluation of High Velocity Impact Resistance of Two-way RC Slab Reinforced with Steel Fiber and FRP Sheet

Abstract: This paper presents high-velocity impact analysis of two-way RC slabs, including steel fibers and strengthening with fiber reinforced polymer (FRP) sheets for evaluating impact resistance. The analysis uses the LS-DYNA program, which is advanced in impact analysis. The present analysis was performed similarly to the high-velocity impact tests conducted by VTT, the technical research center of Finland, to verify the analysis results. High-velocity impact loads were applied to 2100×2100×250 mm size two-way RC sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The outcome of the study showed that the rate-sensitive microplane model strongly simulated the impact of the mechanical response of the RC beams. In another study, which was conducted by Lee et al [22,23], the high-speed impact course of the FRP-RC slab, as well as the steel fiber RC slab, were simulated using the finite element method software, and a conclusion was drawn which showed that the FRP and steel fibers are capable of diminishing the impact dynamic response in the plate, while also improving the impact resistance of the component. Zhao and Qian [24] created a 3D FE model of the earlier test and studied the effects of impact mass, span-depth ratio, and impact velocity on the impact behavior of RC beams.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of the study showed that the rate-sensitive microplane model strongly simulated the impact of the mechanical response of the RC beams. In another study, which was conducted by Lee et al [22,23], the high-speed impact course of the FRP-RC slab, as well as the steel fiber RC slab, were simulated using the finite element method software, and a conclusion was drawn which showed that the FRP and steel fibers are capable of diminishing the impact dynamic response in the plate, while also improving the impact resistance of the component. Zhao and Qian [24] created a 3D FE model of the earlier test and studied the effects of impact mass, span-depth ratio, and impact velocity on the impact behavior of RC beams.…”
Section: Introductionmentioning
confidence: 99%
“…To study the influence of strain rate on the strength, stiffness, and ductility of RC beams, Ozbolt [21] simulated the three-dimensional RC beams with different shear reinforcement ratios and found that the developed rate-sensitive microplane model could well simulate the impact mechanical behavior of the RC beams. Lee [22,23] used the finite element method (FEM) software to simulate the highspeed impact process of FRP-RC slab and steel fiber RC slab and found that FRP and steel fiber can reduce the impact dynamic response in the plate and enhance the impact resistance of the component. Zhao [24] established a 3D FEM model of the previous test, and the effects of impact velocity, impact mass, and span-depth ratio on the impact response of the RC beams were studied.…”
Section: Introductionmentioning
confidence: 99%